Individual taxpayers’ attitude and compliance behaviour in Nigeria: The moderating role of financial condition and risk preference - Alabede, James O. (Academic Journals, 2011)
A number of factors may be responsible for low compliance in income tax administration in Nigeria.However, taxpayers’ attitude has been identified as one factor that play important role in influencing tax compliance behaviour.Besides, the influence of taxpayers’ attitude on compliance behaviour may be moderated by financial condition and risk preference.This study investigated the moderating effect of financial condition and risk preference on relationship between taxpayers’ attitude and compliance behaviour. The data of the study, which were collected through a survey of individual taxpayers’ opinion, were treated statistically using moderated multiple regression. The result of the study indicates that taxpayer’s attitude towards tax evasion is positively related to compliance behaviour. Furthermore, the study also reveals that taxpayer’s risk preference has strong negative moderating impact on the relationship between attitude towards tax evasion and compliance behaviour.